Effect of hot water treatment on postharvest disease development and postharvest quality of sweet potato (Ipomoea batatas) - Suhaizan L.; Nursuraya M.A.; Nurul Faziha I. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Postharvest losses is a major constraint for sweet potato (Ipomea batatas) production in Malaysia. The loss is very often initiated by pathogen infection during storage. The efficacy of hot water treatment (HWT) in preserving the postharvest quality of sweet potato cv. Gendut was investigated in this study. All tubers were treated with HWT (45°C, 50°C and 55°C), subjected to 10 minute and 20 minute immersion time and incubated for 25 days at room temperature (27°C±2°C). Sweet potatoes treated with 50°C for 10 min immersion period showed the lowest score for disease severity, however, it was only effective in reducing disease development but not for the other postharvest qualities assessed. In this study, the application of HWT at 45°C for 10 min immersion time was able to maintain the other postharvest qualities such as weight loss, firmness, titratable acidity and total soluble solid (TSS) of the treated sweet potatoes. It showed that HWT at the temperatures ranging between 45°C to 50°C at 10 min immersion period had the potential in extending the shelf life of sweet potatoes. It reduced the disease severity as well as preserving the important postharvest qualities of sweet potato.